The Influence of Self Efficacy and Self Esteem on Employee Performance Through Motivation as an Intervening Variable - Rifin, Ressa Herdiani; Rosita, Sry; Tialonawarmi, Feny (Management Research and Behavior Journal, 2024)
This research aims to determine the influence of self efficacy and self esteem on employee performance through motivation as an intervening variable at the Jambi Province Food Security Service. This type of research uses quantitative methods. Data collection techniques through distributing questionnaires. The sample in this study was all 97 employees of the Jambi Province Food Security Service. The analysis method in this research is descriptive statistical analysis and uses the Structural Equation Model (SEM) technique with the SmartPLS 4.0 program. The research results show that Self Efficacy has a direct influence on employee performance, Self Esteem has an influence on employee performance, motivation has an influence on employee performance, Self Efficacy has an influence on motivation, Self Esteem has an influence on motivation, Self Efficacy has an influence on employee performance through motivation as an intervening variable, and Self Esteem has an influence on employee performance through motivation as an intervening variable.